Prevalence of Hypertension and its Associated Factors Among Malaysian Staff of Universiti Putra Malaysia - Bezenjani, Somayeh Aminizadeh (2011)
Hypertension is one of the most commonly recognized and treatable risk factors for Cardiovascular Diseases. A cross-sectional study was conducted to determine the prevalence of hypertension and its associated factors among Malaysian staff, aged 30 years old and above in Universiti Putra Malaysia. A simple random sampling technique was used to select the respondents. The data were collected from 28th February 2010 to 5th May 2010 using a selfadministered, pre-tested questionnaire. Two blood pressure measurements were taken from all of the respondents. The respondents were defined as being hypertensive if they had a mean SBP of 140 mmHg and above, and/or a mean DBP of 90 mmHg and above, and/or by self-reports of medical diagnosis of hypertension and current treatment for hypertension with antihypertensive medication. The response rate was 73.2%. Among the respondents the overall prevalence of hypertension was 34.4%. Prevalence of hypertension was higher among males, less educated respondent, those with high family income, those with positive family history of hypertension and those who were obese, former smokers, and physically inactive. Hypertensive respondents were significantly older than normotensive respondents (50.5 vs 38.9 years; p<0.001). The results showed male respondents had significantly higher mean systolic (t= 5.787, p<0.001) and mean diastolic blood pressure (t = 5.962, p<0.001) than female respondents. Of the hypertensive respondents, 64.1% were aware of their condition, among those aware 86% were treated with antihypertensive drugs. However, there were only 45.3% of the treated hypertensive respondents with controlled blood pressure which is less than 140/90 mmHg. Results of logistic regression showed that the respondents at the age group of 40-49, 50-59 and ≥60 years were 5.55, 21.87 and 61.37 times more likely to have hypertension compared to respondents at age group of 30-39 years, respectively. Being male increased the odds of having hypertension by 87% compared to being female. Those with positive family history of hypertension were 5.25 times more likely to have hypertension compared to those with no family history. The odds of having hypertension increased by 3.54 and 11.37 times if a person were overweight and obese, respectively, compared to a normal/underweight person. Being former drinker and current drinker increased the odds of having hypertension by 2.23 and 7.14 times compared to being never drinker, respectively. This rather high prevalence of hypertension implies the importance of the need that university authority should put their effort into action, for example, by organizing an educational campaign for hypertension prevention and control among staff. Keywords: Prevalence, Hypertension, Associated factors, Malaysian staff UPM